AKSESIBILITAS INDUSTRI PANGAN SKALA MIKRO KECIL TERHADAP SUMBER PEMBIAYAAN FORMAL DI KABUPATEN BOGOR - Lillah Wedelia; Manuntun Parulian Hutagaol; Arief Daryanto (Jurnal Agribisnis Indonesia, 2017)
The food industry is one of the small micro enterprises that have a role as a source of employment and incomes. The development of food industry have some problems, especially the lack of accessibility to formal credit institutions. The objectives of this study are to assess the characteristics of food industry and to identify the factors affecting accessibility food industry using the probit models. Result of the study show that the assets and education are an important factor in accessing credit to formal credit institutions.